High sensitivity measurements of the CMB power spectrum with the extended Very Small Array - Dickinson, C; Battye, R; Cleary, K; Davies, R; Davis, R; Genova-Santos, R; Grainge, K; Gutierrez, C; Hafez, Y; Hobson, M; Jones, M; Kneissl, R; et al. (2004)
We present deep Ka-band ($ν ≈ 33$ GHz) observations of the CMB made with the extended Very Small Array (VSA). This configuration produces a naturally weighted synthesized FWHM beamwidth of $\sim 11$ arcmin which covers an $\ell$-range of 300 to 1500. On these scales, foreground extragalactic sources can be a major source of contamination to the CMB anisotropy. This problem has been alleviated by identifying sources at 15 GHz with the Ryle Telescope and then monitoring these sources at 33 GHz using a single baseline interferometer co-located with the VSA. Sources with flux densities $\gtsim 20$ mJy at 33 GHz are subtracted from the data. In addition, we calculate a statistical correction for the small residual contribution from weaker sources that are below the detection limit of the survey. The CMB power spectrum corrected for Galactic foregrounds and extragalactic point sources is presented. A total $\ell$-range of 150-1500 is achieved by combining the complete extended array data with earlier VSA data in a compact configuration. Our resolution of $Δ \ell ≈ 60$ allows the first 3 acoustic peaks to be clearly delineated. The is achieved by using mosaiced observations in 7 regions covering a total area of 82 sq. degrees. There is good agreement with WMAP data up to $\ell=700$ where WMAP data run out of resolution. For higher $\ell$-values out to $\ell = 1500$, the agreement in power spectrum amplitudes with other experiments is also very good despite differences in frequency and observing technique.